Students’ Cognitive Strategies in Learning to Write a Procedure Text - Khuril Aini Sri (Journal of English Education and Literature, 2024)
This study aims to identify cognitive strategies used by students when writing procedural texts and analyze the obstacles that students often experience during the writing process. This study used descriptive qualitative research method and was conducted at SMPN 13 Mataram involving 3 informants who were selected using purposive sampling technique. The instruments of this research were interviews, notes, and voice recorders. Researchers collected data using semi-structured interview techniques and the raw data was analyzed using four procedures, namely data collection, data compaction, data presentation, and conclusion drawing. The result of this research, it was found that the problems experienced by students were grammatical constraints, lack of vocabulary, and cognitive problems. This research also shows that students use elaboration strategies to overcome obstacles in the areas of grammar, vocabulary, and spelling, organization strategies are used by students for language problems or word selection and finally rehearsal strategies by memorizing or remembering vocabulary are used when they have difficulty in choosing or using vocabulary when writing procedure text. In conclusion, in writing the constraints experienced by students are grammatical constraints, lack of vocabulary, and cognitive problems. Students use 3 types of cognitive strategies in overcoming these obstacles, namely rehearsal, organization and elaboration by using these strategies students can complete their task of writing procedure text.